Impulsionamento de uma biblioteca virtual por meio de um plano de marketing: estudo de caso na UFMT - Moreno, Olgarita Helena da Silva (Universidade Federal de São Carlos, 2025)
The advancement of telecommunications and information technology has profoundly transformed human relations, impacting work, learning processes, and access to knowledge. In this context, libraries play a strategic role in information dissemination and are challenged to adapt to the dynamics of the digital era. The emergence of virtual libraries and digital books represents a significant innovation, expanding access to documentary records and strengthening remote support for teaching, research, and extension activities in higher education institutions. Despite these potentialities, reports from companies contracted by the Federal University of Mato Grosso (UFMT) indicate a low level of use of virtual platforms compared to the number of available licenses. In contrast, the empirical data of this research, obtained through questionnaires applied to 124 undergraduate students and 55 faculty members (totaling 179 respondents), reveal that most participants are aware of and report using virtual libraries, although in an irregular and uneven manner across courses and campuses. This mismatch indicates that the issue lies not only in lack of awareness but, above all, in the absence of effective institutional strategies for mediation, dissemination, and integration of these resources into academic practices. Based on this diagnosis, the research—characterized as a case study—resulted in the development of a marketing plan aimed at boosting the use of UFMT’s virtual libraries, constituting a technological product of the Professional Master’s Degree in Production Engineering. Among the main results, the study highlights the identification of barriers related to institutional communication, user training, and faculty engagement, as well as the proposal of targeted strategic actions, such as segmented campaigns, continuous training initiatives, integration of platforms into course syllabi, and strengthening of informational mediation. It is concluded that strengthening virtual libraries depends on coordinated action among institutional management, technical staff, and faculty, in order to transform the available informational potential into effective, continuous, and qualified use. By identifying gaps and proposing concrete interventions, this study contributes not only to expanding access to and use of virtual libraries at UFMT but also provides replicable insights for other higher education institutions facing similar challenges in the context of digital culture.
Boosting a virtual library through a marketing plan: a case study at UFMT
Keywords: Bibliotecas virtuais da UFMT; Marketing em bibliotecas universitárias; Plano de Marketing; Mediação informacional; Comunicação institucional; Ensino superior; Virtual libraries of UFMT; Marketing in university libraries; Marketing plan; Information mediation; Institutional communication; Higher education; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; 17. Parcerias e Meios de Implementação